ОСОБЛИВОСТІ ПОБУДОВИ КОМПОНЕНТІВ БАГАТОРІВНЕВИХ ЕКСПЕРТНИХ СИСТЕМ ВІБРОДІАГНОСТИКИ ВУЗЛІВ ЕЛЕКТРОТЕХНІЧНОГО ОБЛАДНАННЯ З УРАХУВАННЯМ ВИКОРИСТАННЯ БЕЗДРОТОВИХ БЛОКІВ ЗВ'ЯЗКУ - Гижко, Ю.І.; Зварич, В.М. (Інститут електродинаміки НАН України, Київ, 2024)
Some peculiarities of construction of elements of wireless communication channels, which are part of multilevel information and measuring systems for diagnosing electrical equipment, are considered. One of the possible options for constructing the primary measurement channel, focused on the use of wireless measurement sensors that are consistent with international standards, is considered. A brief description of possible diagnostic features for determining the technical condition and classification of possible defects in individual components of electrical equipment is given. References 21, figures 1.